(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Kindergarten is an educational program designed to mold children for school by giving numerous games activities. In fact, many learning materials and strategies were already implemented to enhance the learner’s skills and understanding. Thus, this study aimed to assess the proficiency of Kindergarten learners in Luna I District as an input in crafting an integrated learning package. Specifically, it looked into the proficiency of kindergarten learners along with the gross motor domain, fine motor domain, self-help domain, receptive language domain, expressive language domain, cognitive domain; and social-emotional domain: the least mastered kindergarten competencies along the seven (7) domains were the basis of the proposed integrated learning package for Kindergarten learners. The study utilized the descriptive method of research with the researcher-made questionnaire as the tool for gathering data from the 135 respondents. The data gathered were treated statistically using frequencies, means, and percentages. It was found that the respondents were proficient in all the seven (7) domains of learning. Meanwhile, the least mastered domains were cognitive and expressive language. It is concluded that kindergarten learners need numerous opportunities to engage in classroom learning for their proficiency in all seven learning domains to be developed. Carefully planned activities can address the least mastered competencies of kindergarten learners. Hence, the Integrated Learning Package for Kindergarten Learners is implementable.